2005
DOI: 10.1111/j.1365-2826.2005.01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the Type‐2 Gonadotrophin‐Releasing Hormone (GnRH) Receptor Mediates the Behavioural Effects of GnRH‐II on Feeding and Reproduction in Musk Shrews

Abstract: Gonadotrophin-releasing hormone (GnRH) is a regulatory neuropeptide of which there are multiple structural variants. In mammals, a hypothalamic form (GnRH-I) controls gonadotrophin secretion whereas a midbrain form (GnRH-II) appears to have a neuromodulatory role affecting feeding and reproduction. In female musk shrews and mice, central administration of GnRH-II reinstates mating behaviour previously inhibited by food restriction. In addition, GnRH-II treatment also decreases short-term food intake in musk sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 46 publications
(92 reference statements)
3
60
0
Order By: Relevance
“…11) [137]. Moreover, an antagonist at the type I GnRH receptor which is an agonist at the type II GnRH receptor (antagonist 135-18 stimulates reproductive behavior in female musk shrews suggesting that the effect is mediated by the type II receptor [60]. This conclusion is further supported by the demonstration that antide which is an antagonist at the type I receptor but is inactive at type II receptors, had no effect on GnRH II stimulation of behavior.…”
Section: Gnrh II As a Regulator Of Reproductive Behaviormentioning
confidence: 88%
See 1 more Smart Citation
“…11) [137]. Moreover, an antagonist at the type I GnRH receptor which is an agonist at the type II GnRH receptor (antagonist 135-18 stimulates reproductive behavior in female musk shrews suggesting that the effect is mediated by the type II receptor [60]. This conclusion is further supported by the demonstration that antide which is an antagonist at the type I receptor but is inactive at type II receptors, had no effect on GnRH II stimulation of behavior.…”
Section: Gnrh II As a Regulator Of Reproductive Behaviormentioning
confidence: 88%
“…This conclusion is further supported by the demonstration that antide which is an antagonist at the type I receptor but is inactive at type II receptors, had no effect on GnRH II stimulation of behavior. Interestingly, these effects could only be demonstrated after food restriction and GnRH II itself was found to inhibit feeding behavior in musk shrews [59,60]. Thus, it appears that under normal conditions when animals are satiated the endogenous GnRH II system is fully activating reproductive behavior and exogenous GnRH II is not required.…”
Section: Gnrh II As a Regulator Of Reproductive Behaviormentioning
confidence: 99%
“…decline of circulating LH and testosterone, however can be reversed rapidly upon feeding, suggesting that there is a calorie-dependent regulation of GnRH pulse-generator output (Aloi et al, 1997). Further linking GnRH function, there is evidence of not only GnRHs role in generic neuronal excitability during fasting (Röjdmark, 1987), controlling the desire behind food intake (Kauffman et al, 2005a), but there is also evidence that food intake itself directly controls the mRNA and protein levels of GnRH in mammalian brains (Kauffman et al, 2006). It has been shown that even short periods of dietary energy deprivation (24-72 h) can have dramatic effects upon the hypothalamic-pituitary-gonadal (HPG) axis in humans and animal models.…”
Section: Ghrelin and Growth Hormonementioning
confidence: 99%
“…In contrast, when females are on ad libitum diets or they are food restricted, acute infusions of GnRH II depressed food intake (Kauffman, Wills, Millar, and Rissman, 2005). Since GnRH II is an evolutionarily conserved neuropeptide found in various vertebrates and non-vertebrate species, it is possible that it interacts with some of the other highly conserved hypothalamic peptides that modulate feeding behavior; such as NPY.…”
Section: Discussionmentioning
confidence: 99%